Princípios estruturantes do processo legislativo e pandemia de Covid-19: análise dos seus impactos na Assembleia de Minas - Marcelo Fonseca Ribeiro de Castro (2023)
The Covid-19 pandemic presented a number of challenges to humanity, and to parliamentary work one in particular: how to continue legislative production, especially necessary in an unusual context, maintaining physical distance and applying the structuring principles of the legislative process, including the guarantee of equality among peers? In the Legislative Assembly of Minas Gerais, based on an existing loophole in the Internal Regulations, the option was to make the necessary adaptations in the process through decisions of the Board, either accepting Leaders' Agreements or in the form of Board Deliberations, a normative instrument hitherto used only for regulations of an administrative nature. Although there was a consensus that eliminated (almost) all conflicts, there was high productivity in the Minas Gerais’ parliament, based on a summary proceeding that may and should be criticized, mainly from the point of view of guaranteeing voice and participation. Among the innovations of what was later called the “Covid proceeding”, for example, we had the prohibition of submitting incidental requests and the detachment (and considerable reduction of time) of the discussion from the moment of votation, without the possibility of presenting an amendment after concluding the discussion. The present work, therefore, aims to record this unique moment in history based on the critical analysis of the 20 infra-regimental norms that modified the legislative process in the State, taking a look also at what remained unchanged, in an attempt to identify, from the structuring principles of the legislative process, the essentialities to which the Internal Regulations of the Assembly refer. By doing so, we expect to move towards defining the limits of the future Leaders' Agreements, providing technical assistance to the representatives with greater legal security and contributing to the consequent strengthening of democracy.